Medical pluralism amongst Makhanda traditional health practitioners: Exploring dispositions to COVID-19 vaccinations - Mothapo, Lebogang (Rhodes University, Faculty of Humanities, Department of Anthropology)
Healers and healing', 'wellbeing and prevalence', 'medical systems and progression'. Every healing concept is tied to people's perspectives, thoughts, beliefs, and backgrounds. Worldviews and world perspectives influence these throughout time and space. The progressive postulation between medical systems and the comprehensive relations between them is a narrative worth exploring through the distinct perspectives of Traditional Health Practitioners in Makhanda. This qualitative study sought to explore the dispositions of Traditional Health Practitioners (THPs) towards COVID-19 vaccinations to understand the practice and acceptance of medical pluralism through a traditional lens. Through purposive and snowball sampling, 10 participants were recruited and semi-structured in-depth interviews were conducted as a tool for data collection. Thematic data analysis was conducted to analyse the data, and multiple codes that led to themes emerged. THPs exhibit multiple concepts tied to COVID-19 vaccination, representing the dynamic understanding of participating in biomedical approaches. THPs, in their decision to uptake the COVID-19 vaccination, are motivated by the severity of the disease and other compelling reasons, such as the obligations and regulations put in place to encourage vaccination uptake in achieving mass/herd immunity. THPs who, in their decision of not uptaking the COVID-19 vaccination, display mistrust, disregard for the COVID-19 vaccination in particular and the entrusted commitment to traditional medicine. In all the expressed dispositions, reliance on the understanding of COVID-19 and the dependence on lived experiences played an integral role in how THPs responded to COVID-19 vaccinations. Due to this understanding, the practice of medical pluralism amongst Makhanda THPs is understood through context-based concepts to explore the in-depth multifaceted positioning of medical pluralism.
Keywords: Traditional healer -- Attitudes; Integrative medicine; COVID-19 vaccines; COVID-19 Pandemic, 2020-2023 Influence; Traditional healer -- South Africa -- Makhanda